Methods of reduction of control objects models containing oscillating and forcing links - A. G. Stryzhnev; A. A. Shykhau (Системный анализ и прикладная информатика)
Methods of reduction of control objects models containing oscillating and forcing links are proposed. Methods are based on using of quadratic equation modulus and coefficient of factorization that makes links discriminants equal or more than zero. Methods allow taking into account transfer factors alterations during reduction of objects models ant to maximum simplify quadratic equations of oscillating and forcing links. The order of reduced objects models is decreased and models behavior closely agrees with behavior of the original model. In that case synthesis of controllers is essentially simplified. Such controllers provide slight overshoot (less than 10–17%) during the work within control system. It can be reduced by changing of system gain. Examples of reduction of real control objects models and examples of synthesis of digital controllers and results of modelling are given.